FAST Method to Design Web-Based Patient Registration System - Pratama, Mudafiq Riyan; Alfiansyah, Gamasiano; Swari, Selvia Juwita (Indonesian Journal Publisher, 2024)
Manual patient registration at the Polyclinic of Politeknik Negeri Jember (POLIJE) offers ineffectiveness in the patient services. Long waiting time and uninformed service hours at the polyclinic are two problems that need to solve. This study aimed to design a website-based registration system for the POLIJE Polyclinic. The researcher used the FAST (Framework for the Application of System Thinking) method. This method has detailed stages and is capable of producing more efficient, effective, accurate and timely data and information management. The application was built using PHP programming language with Laravel Framework. The registration system was implemented using RFId on patient cards to make the process of reading and registering patient data faster. The web-based registration system with RFId patient cards functions well with features: new patient registration, registration of patient visits with RFId cards, patient queues, verification of patients who register online, as well as patient, doctor and clinic data management.